2006
DOI: 10.1111/j.1467-9280.2005.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Purchases of Food in Youth

Abstract: One way to increase choice of healthy over unhealthy behaviors is to increase the cost of less healthy alternatives or reduce the cost of healthier alternatives. The influence of price on purchases of healthy and unhealthy foods was evaluated in two laboratory experiments. In Experiment 1, thirty-two 10- to 12-year-old youth were given $5.00 and allowed to purchase multiple portions of a healthy food (fruit or vegetable) and a less healthy food (higher-fat snack). The price of one type of food varied from $0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…Autonomy, food accessibility and food availability have been shown to influence schoolchildren's dietary intakes (18,34). Schoolchildren will eat foods sold by vendors within the school precincts (35) and they will eat more fruits when these are free or cheap (34,36). Similarly, low price acts as incentive for unhealthy food consumption (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autonomy, food accessibility and food availability have been shown to influence schoolchildren's dietary intakes (18,34). Schoolchildren will eat foods sold by vendors within the school precincts (35) and they will eat more fruits when these are free or cheap (34,36). Similarly, low price acts as incentive for unhealthy food consumption (34).…”
Section: Discussionmentioning
confidence: 99%
“…Schoolchildren will eat foods sold by vendors within the school precincts (35) and they will eat more fruits when these are free or cheap (34,36). Similarly, low price acts as incentive for unhealthy food consumption (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear way to increase healthy choices over unhealthy choices is to provide an economic incentive by, for example, healthy food subsidies and unhealthy food taxes. It was shown that young individuals do respond to this, with price rises reducing purchases of a particular food, and substitution between healthy and unhealthy foods occurring as prices rise or fall depending on the amount of disposable income 190 .…”
Section: The Macro-environmentmentioning
confidence: 99%
“…13 Experimental work has found that children decrease their consumption of certain foods when the price is increased. 14 Living in areas with higher-priced fast foods and soda is associated with lower body weight and BMI, whereas higher fruit and vegetable prices demonstrate the opposite association. [15][16][17][18][19][20][21][22] These relationships appear to be larger among low-income children as compared with their higherincome counterparts, 15,17,18 presumably because their families have less disposable income.…”
mentioning
confidence: 99%